The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1371/journal.pone.0182538
|View full text |Cite
|
Sign up to set email alerts
|

Normative weight-adjusted models for the median levels of first trimester serum biomarkers for trisomy 21 screening in a specific ethnicity

Abstract: ObjectiveTo establish normative weight-adjusted models for the median levels of first trimester serum biomarkers for trisomy 21 screening in southern Thai women, and to compare these reference levels with Caucasian-specific and northern Thai models.MethodsA cross-sectional study was conducted in 1,150 normal singleton pregnancy women to determine serum pregnancy-associated plasma protein-A (PAPP-A) and free β-human chorionic gonadotropin (β-hCG) concentrations in women from southern Thailand. The predicted med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…Moreover, our study and previous studies have shown that race and ethnic factors have an important effect on serum concentrations both in DS and normal fetuses throughout the gestational period [7,[10][11][12]20]. Another study from our institution reported the same evidence from first trimester serum screening for DS [21]. Maternal serum quadruple markers do not have universally applicable levels for screening for DS in all races and ethnicities, and have also been reported in other studies which found differences in normative median serum levels in subgroups of the same country or ethnicity [14,20].…”
Section: Plos Onesupporting
confidence: 85%
“…Moreover, our study and previous studies have shown that race and ethnic factors have an important effect on serum concentrations both in DS and normal fetuses throughout the gestational period [7,[10][11][12]20]. Another study from our institution reported the same evidence from first trimester serum screening for DS [21]. Maternal serum quadruple markers do not have universally applicable levels for screening for DS in all races and ethnicities, and have also been reported in other studies which found differences in normative median serum levels in subgroups of the same country or ethnicity [14,20].…”
Section: Plos Onesupporting
confidence: 85%